ISOLATION OF THERMOPHILIC LIPASE PRODUCING BACTERIUM FROM HOT SPRINGS AT THE EAST COAST OF PENINSULAR MALAYSIA - Tengku Haziyamin Tengku Abdul Hamid; Nur Asimah Zainal Abidin; Nurmusfirah Hasan (Journal of Tropical Life Science, 2021)
Hot spring is a natural habitat for thermophilic bacteria and is the major source of thermostable enzymes useful in industrial application. In Malaysia, the search for thermophilic organisms have been focused on hot springs especially on the west coast of the peninsular. In this work, lipase producing thermophilic microorganisms were isolated from east coast hot springs in the states of Pahang and Terengganu. All of the 7 isolates showed the ability to grow at 45Â°C and formed lipolytic zones on tributyrin agar plates. However, only isolate B2B2 and S1B4 were able thrive at higher temperatures of up to 65Â°C. Bacillus and Geobacillus species was found to be the dominant bacterium isolated from these hot springs. From La hot spring, isolate L1 (MT 645486), LH2, (MT645483), LH3 (MT645484), LH4 (MT 645485) and LH5 (MT 645487) were all closely related to Bacillus sp. (94 to 97%). Meanwhile, from Bentong and Sungai Lembing hot springs, isolates B2B2 (MT668631) and S1B4 (MT668632) were closely related to Geobacillus kaustophilus (98.5%) and Geobacillus thermoleovorans (98%), respectively. Strains from Geobacillus sp. were able to thrive at higher temperature and their thermostable lipases have properties useful for biotechnological applications.